2009
DOI: 10.1158/1078-0432.ccr-08-2023
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma Variants: Age-Dependent Occurrence and Relation to Gorlin Syndrome—A New Clinical Perspective

Abstract: Purpose: We aimed to test the hypothesis that medulloblastoma (MB) variants show a different age distribution and clinical behavior reflecting their specific biology, and that MB occurring at very young age is associated with cancer predisposition syndromes such as Gorlin syndrome (GS). Experimental Design: We investigated the frequency, age distribution, location, response to treatment, outcome, and association with familial cancer predisposition syndromes in a series of 82 cases of MB in patients ages <14 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 48 publications
5
65
0
4
Order By: Relevance
“…In a large prospective study of MBs, Eberhart et al [18] reported that 14 out of the 330 cases examined were MBEN (4.2%). Diagnostic criteria for MBEN are: >50% of analyzed tissue samples contain prominent nodularity, along with intranodular nuclear uniformity in a desmoplastic background [19]. The nodularity can be so profound that it may be visualized on MRI as a ‘grape-like’ mass.…”
Section: Discussionmentioning
confidence: 99%
“…In a large prospective study of MBs, Eberhart et al [18] reported that 14 out of the 330 cases examined were MBEN (4.2%). Diagnostic criteria for MBEN are: >50% of analyzed tissue samples contain prominent nodularity, along with intranodular nuclear uniformity in a desmoplastic background [19]. The nodularity can be so profound that it may be visualized on MRI as a ‘grape-like’ mass.…”
Section: Discussionmentioning
confidence: 99%
“…Another example come from the mutations in SUFU (a tumour suppressor gene controlling the Sonic hedgehog signalling) which most remarkably predispose to early onset desmoplastic medulloblastomas, before 3 years of age. 6,7 Peripheral neuroblastic tumours are tumours of neural crest origin that mostly affect children before 5 years of age. The young age at diagnosis lead Knudson and Strong 8 to propose that neuroblastic tumours might frequently arise in a predisposition context.…”
Section: Introductionmentioning
confidence: 99%
“…54 It has been suggested that young children presenting with medulloblastoma of nodular or desmoplastic histology need to be assessed for GS. 54,55 In PTCH1-negative children younger than the age of 3 years with a desmoplastic/nodular medulloblastoma, with and without other manifestations fitting GS, germline mutations in suppressor of fused homolog (SUFU) have been identified. Nontumor CNS manifestations include 56 Both the presence of a germline mutation (in 85% of patients who fulfil the diagnostic criteria of CS a mutation is identified) and the location of the mutation are associated with severity of disease.…”
Section: Gorlin Syndromementioning
confidence: 99%